Modified Tumescent Solution for Creating Working Space During Endoscopic Thyroidectomy. (April 2018) - Zhang, Li-Yong; Zhao, Wen-Xin; Wang, Bo; Yan, Shou-Yi; Wen, Jia
Objective . To study the feasibility of gas-liquid mixing tumescent solution for creating a working space (WS) in endoscopic thyroidectomy (ET). Materials and Methods . A prospective study was performed on 186 patients with thyroid tumor who had undergone ET via chest and breast approach. Patients were randomly divided into 2 groups to receive traditional tumescent solution as group A and modified tumescent solution (gas-liquid mixing tumescent solution) as group B. This study compares the following surgical outcome parameters between the 2 groups, including changes of blood pressure, heart rate, and oxygen saturation before and after creating a WS, time for creating a WS, operative time, hemorrhage volume for creating a WS, overall hemorrhage volume, overall postoperative drainage volume, postoperative pain score, postoperative hospitalization, number of retrieved lymph nodes, total serum calcium, serum parathyroid hormone, and cases of transient and permanent recurrent laryngeal nerve palsy. Results . No postoperative bleeding, permanent recurrent laryngeal nerve palsy, incision and surgical site infection, air embolism, flap injury occurred in both groups. The mean time for creating a WS and the whole operation in group B was significantly shorter than that in group A ( P < .05). There were no statistically significant differences in both groups in terms of other observation index ( P > .05). Conclusion . The clinical application of gas-liquid mixing tumescent solution can effectively reduce the time for creating a WS and whole operative time, and worthy of being widely used in ET as a safe and effective technique.